The law of refugee status - Hathaway, James C.; Foster, Michelle, 1972- (Cambridgs : Cambridgs University Press, 2014)
"Refugee law may be the world's most powerful international human rights mechanism. Not only do millions of people invoke its protections every year in countries spanning the globe, but they do so on the basis of a self-actuating mechanism of international law that, quite literally, allows at-risk persons to vote with their feet. This is because, as the United Nations High Commissioner for Refugees ("UNHCR") has insisted, refugee status is not a status that is granted by states; it is rather simply recognized by them"--
Includes bibliographical references and index.
Keywords: Refugjatët = Refugees; Legjislacioni = Legislation; Politika = Politics